2012
DOI: 10.1007/s10517-012-1666-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Multipotent and Retinal Markers in Pigment Epithelium of Adult Human in Vitro

Abstract: Immunoperoxidase and molecular genetic analysis showed that retinal pigment epithelial cells from adult human eye undergo morphogenetic changes in vitro. They lose expression of tissue-specific protein RPE65 and start to express stem cell markers: Oct4 (POU5F1), Nanog, Prox1, Musashi 1, and Pax6, which indicates their differentiation. Expression of Musashi 1 and Pax6 attest to neural differentiation, which is also confirmed by the expression of βIII-tubulin, a neuroblast marker, and markers of differentiated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…CRALBP, RPE65 and RDH5 were abundant in native and absent in cultured RPE cells. Correlating with our results, former research observed that RPE65 and CRALBP, both proteins associated with highly specialized functions of the RPE, were absent in cultured RPE cells [14,30]. Regarding that CRALBP is not only expressed by RPE cells, but also, for instance, by Mueller glial cells [31], we believe that RPE65 is an excellent marker for the verification of native in comparison to cultured RPE, as it was found to be differentially expressed by Western blot analysis, immunocytochemistry and even PCR (Figure 2–4).…”
Section: Discussionsupporting
confidence: 91%
“…CRALBP, RPE65 and RDH5 were abundant in native and absent in cultured RPE cells. Correlating with our results, former research observed that RPE65 and CRALBP, both proteins associated with highly specialized functions of the RPE, were absent in cultured RPE cells [14,30]. Regarding that CRALBP is not only expressed by RPE cells, but also, for instance, by Mueller glial cells [31], we believe that RPE65 is an excellent marker for the verification of native in comparison to cultured RPE, as it was found to be differentially expressed by Western blot analysis, immunocytochemistry and even PCR (Figure 2–4).…”
Section: Discussionsupporting
confidence: 91%
“…In cell culture, RPE cells lose their original features, such as pigmentation, significantly reduce the expression of specific markers RPE65, MITF, and CRALBP and acquire features of neural cells on markers MUSASHI1, NESTIN, βIII-TUBULIN, GFAP, DOUBLECORTIN, and NF 68 and 200 kDa. Our studies also demonstrate that RPE cells of the human embryo and adult in vitro in media with the addition of morphogens and growth factors lose their pigment granules, dedifferentiate, proliferate, and exhibit markers of several types of neural and glial cells (Milyushina et al, 2009(Milyushina et al, , 2011(Milyushina et al, , 2012Kuznetsova et al, 2014;Kuznetsova et al, 2015Kuznetsova et al, , 2019. At the dedifferentiation stage, cells acquire stem/neuroepithelial cell traits by expressing OCT4, NANOG, KLF4, OTX2, PAX6, and NESTIN (Milyushina et al, 2009Kuznetsova et al, 2014Kuznetsova et al, , 2015Kuznetsova et al, , 2019aKuznetsova et al, , 2019b.…”
Section: Ash1 Ath3 Chx10supporting
confidence: 63%
“…In the cell culture conditions, RPE cells under the influence of specific inducers show signs not only of neural but also of smooth muscle, adipo-, chondro-, and osteogenic differentiation. According to some authors, RPE cells under certain conditions can become "multipotent stem cells" capable of producing cells of both neural and mesenchymal phenotypes (Milyushina et al, 2012;Salero et al, 2012). The capability for multiple differentiations emphasizes the interest in the extremely high plasticity of RPE cells and sets the task of searching for mechanisms that determine it and of factors for regulating directed differentiation.…”
Section: Ash1 Ath3 Chx10mentioning
confidence: 99%
“…Our immunohistochemical and molecular genetic studies on primary cultures of adult human RPE cells have shown that they begin to express stem cell gene markers such as Oct4 (POU5F1), Nanog, Prox1, Musashi 1, and Pax6 , which is evidence for dedifferentiation of RPE cells in the course of culturing [87]. Moreover, these cells are capable of subsequent transdifferentiation into neural cells, as indicated by the expression of Musashi 1, Pax6, and TUBB3 (Figure 1(a)) and positive staining with antibodies against protein markers of neuronal differentiation—nestin, TUBB3 (Figure 1(b)), tyrosine hydroxylase, neurofilaments 68 and 200 (Figure 1(c)), and nNOS—and glial differentiation (CNPase, GFAP) [25, 26, 87, 88].…”
Section: Approaches To Human Rpe Cell Culturingmentioning
confidence: 99%
“…Moreover, these cells are capable of subsequent transdifferentiation into neural cells, as indicated by the expression of Musashi 1, Pax6, and TUBB3 (Figure 1(a)) and positive staining with antibodies against protein markers of neuronal differentiation—nestin, TUBB3 (Figure 1(b)), tyrosine hydroxylase, neurofilaments 68 and 200 (Figure 1(c)), and nNOS—and glial differentiation (CNPase, GFAP) [25, 26, 87, 88]. RPE cells in vitro also show positive staining for vimentin, a marker of intermediate filaments [26, 73].…”
Section: Approaches To Human Rpe Cell Culturingmentioning
confidence: 99%